Shining light on magnetic monopoles through high-energy muon colliders - Ji-Chong Yang; Yu-Chen Guo; Bing Liu; Tong Li (Nuclear Physics B, 2023)
The search for magnetic monopoles has been a longstanding concern of the physics community for nearly a century. However, up to now, the existence of elementary magnetic monopoles remains an open question. The electroweak 't Hooft-Polyakov monopoles have been predicted with mass at the order of 10 TeV. This mass scale is unreachable at current colliders. Recently, the muon colliders have gained much attention in the community due to technological developments. The advantages of the muon beam encourage us to raise the high-energy option and consider the high-energy muon collider as a unique opportunity to search for magnetic monopoles. This letter discusses the production of magnetic monopoles via the annihilation process and proposes the search for magnetic monopoles at future high-energy muon colliders.